Poole waste water treatment BAF plant - Brewer, Peter (Cranfield University, School of Water Sciences, 1996)
1. The town of Poole in south east Dorset has undergone substantial development during the 1980's. Wessex Water recognised the pressure on the water services in this region and commissioned a strategy study for this region. This resulted in a proposal to extend each sewage treatment works in that area up to a standard required by the receiving watercourse. 2. The 2 main river catchments are the River Stour and River Avon. The latter flows into Christchurch harbour in the east, whilst the Stour flows into Poole Harbour. Poole WWTW discharges directly into Holes Bay in the upper reaches of Poole Harbour.This tidal estuary is of national importance in environmental terms, whilst being extensively used for recreation. 3. Consultations with the National Rivers Authority (now the Environmental Agency) led to a discharge standard of 20 mg/I BOD; 30 mg/I SS;10 mg/I Amm N on a 95 percentile basis being accepted for design of the extensions. Indications are that in the long term nutrient removal and disinfection may well become a necessity. The EA has plans to conduct extensive surveys of Poole Harbour in the next few years. 4. The extensions to Poole VWVTVV will raise the treatment capacity from a population equivalent of 129,000 to some 151,000. Dry weather flow will be 46,700 m3/d, and flow to full treatment will be 17,700 m3/d at the 12 year planning horizon. These extensions now provide a treatment plant with some 48% increase in hydraulic capacity, whilst producing a fully nitrified effluent. 5. The existing treatment plant consists of essentially two separate plants, known as eastern and western, both activated sludge plants. The site is quite close to the historical town centre, and growth in the town over the last half century has extended well beyond the works site. Consequently, the works is now completely surrounded by development fro housing to light industry. Indeed, we now have the benefit of a major supermarket on our southern boundary, some 20m from the inlet pumping station!